The application of fecal microbiota transplantation in Parkinson’s disease - Wang, Boyan; Ma, Di; Li, Na; Luo, Tianfei (Frontiers in Aging Neuroscience, 2025)
BackgroundParkinson’s disease (PD) is a multisystem neurodegenerative disorder characterized by the aggregation of α-synuclein (α-syn) in dopaminergic neurons of the substantia nigra. The pathogenesis of PD remains incompletely understood, and disease-modifying therapies are lacking. Emerging evidence suggests that gut microbiota and their metabolites influence both intestinal and central nervous system (CNS) functions via the microbiota-gut-brain axis (MGBA). Recent studies have identified dysbiosis in the gut microbiota of PD patients, which may contribute to disease progression through two primary mechanisms: First, increased intestinal permeability, allowing pro-inflammatory factors and microbial metabolites to affect the enteric nervous system (ENS) and subsequently spread to the CNS via the vagal neurons; Secondly, disruption of the Blood–Brain barrier (BBB), leading to neuroinflammation and aberrant α-syn aggregation, ultimately resulting in dopaminergic neuron degeneration. These findings underscore the critical role of the MGBA in PD pathogenesis, which makes gut microbiota modulation a promising therapeutic target.HighlightsThis review synthesizes current knowledge on gut microbiota alterations in PD and evaluates the potential of fecal microbiota transplantation (FMT) as an adjunctive therapy to alleviate motor and non-motor symptoms and slow disease progression.ConclusionFMT has demonstrated efficacy in ameliorating PD symptoms via the MGBA. However, further preclinical and clinical studies are needed to fully elucidate its mechanisms and optimize therapeutic protocols. Targeting the gut microbiota may offer novel biomarkers and intervention strategies for PD.